Brain Bioavailability of Human Intravenous Immunoglobulin and its Transport through the Murine Blood–Brain Barrier. Issue 12 (December 2013) - St-Amour, Isabelle; Paré, Isabelle; Alata, Wael; Coulombe, Katherine; Ringuette-Goulet, Cassandra; Drouin-Ouellet, Janelle; Vandal, Milène; Soulet, Denis; Bazin, Renée; Calon, Frédéric
Intravenous immunoglobulin (IVIg) is currently evaluated in clinical trials for the treatment of various disorders of the central nervous system. To assess its capacity to reach central therapeutic targets, the brain bioavailability of IVIg must be determined. We thus quantified the passage of IVIg through the blood–brain barrier (BBB) of C57Bl/6 mice using complementary quantitative and qualitative methodologies. As determined by enzyme-linked immunosorbent assay, a small proportion of systemically injected IVIg was detected in the brain of mice (0.009±0.001% of injected dose in the cortex) whereas immunostaining revealed localization mainly within microvessels and less frequently in neurons. Pharmacokinetic analyses evidenced a low elimination rate constant (0.0053  per hour) in the cortex, consistent with accumulation within cerebral tissue. In situ cerebral perfusion experiments revealed that a fraction of IVIg crossed the BBB without causing leakage. A dose-dependent decrease of brain uptake was consistent with a saturable blood-to-brain transport mechanism. Finally, brain uptake of IVIg after a subchronic treatment was similar in the 3xTg-AD mouse model of Alzheimer disease compared with nontransgenic controls. In summary, our results provide evidence of BBB passage and bioavailability of IVIg into the brain in the absence of BBB leakage and in sufficient concentration to interact with the therapeutic targets.